ANALISIS PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Rony Arpinto Ady (STIE St. Pignatelli Surakarta, 2021)
This research aims to analyze the financial ratio analysis against to the stock price on the banking companies listed on the Stock Exchange th period 2016-2018. The approach used in this research is quantitative research approach (using data that can be measured in a scale of numeric/numbers), using secondary data in the form of panel data (pooling of data) that combines data coherently time (time series) data and kerat latitude (cros section) in that period of time. The source of the data used in this research is secondary data. Data collection the data archive in the form of secondary data collection techniques using database pooling data retrieval/data panel (combined time series data and cros section). In analyzing the data, researchers using multiple linear regression test. The results showed ROA has a positif and significant relationship towards Stock Price. There is no influence between ROE against Stock Price. NPM has a positif and significant relationship towards Stock Price.